NICU Bereavement Care and Follow-up Support for Families and Staff. (December 2017) - Levick, Judy; Fannon, Jane; Bodemann, Janet; Munch, Shari
Abstract : Background: Experiencing the death of an infant in the neonatal intensive care unit (NICU) affects both families and staff, creating challenges and opportunities for best practices. Purpose: This practice-based article describes a comprehensive approach to delivering bereavement services to NICU families, as well as education and support to NICU staff. Methods: Bereaved NICU parent and staff survey feedback, including quotes describing individual experiences and suggestions for improved service delivery. Results: Bereaved NICU families and caregivers find meaning and purpose in the act of creating keepsake memories at the time of the infant's death. Mutual healing takes place with subsequent, individualized follow-up contacts by staff familiar to the bereaved parents over the course of a year. Implications for Practice: Those staff involved in the care of a NICU infant and family, during and after the infant's death, attest to the value in providing tangible keepsakes as well as continuing their relationship with the bereaved parents. An effective administrative infrastructure is key to efficient program operations and follow-through. Implications for Research: Studying different methods of in-hospital and follow-up emotional support for NICU bereaved families. Identifying strategies for staff support during and after NICU infant loss, and the impact a formal program may have on staff satisfaction and retention.